Nitrogen-doped carbon-based positive electrode host material, preparation method and application thereof

CN122667576BActive Publication Date: 2026-11-03NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611176338.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-11-03
Estimated Expiration
2046-08-05

AI Technical Summary

Technical Problem

Existing aqueous zinc-iodine batteries suffer from problems such as poor conductivity of iodine species, easy sublimation, dissolution and shuttle of multiple iodides, and low coulombic efficiency. Furthermore, existing doping methods are difficult to balance cost and performance.

Method used

A high-temperature gas-phase nitrogen doping strategy was adopted to modify porous carbon materials and construct nitrogen-doped carbon-based cathode host materials. Through the synergistic mechanism of physical confinement and chemical adsorption, the redox kinetics of iodine species were promoted and the formation and shuttle of polyiodide ions were inhibited.

Benefits of technology

A cathode host material with high specific capacity and long cycle life has been developed, reducing costs and improving coulombic efficiency and operational reliability, thus solving a key bottleneck in traditional aqueous zinc-iodine batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122667576B_ABST
    Figure CN122667576B_ABST
Patent Text Reader

Abstract

The application discloses a nitrogen-doped carbon-based positive electrode host material and a preparation method and application thereof. The preparation method comprises the following steps: step 1, pretreating a porous carbon material, drying the porous carbon material to obtain a dried carbon material, uniformly mixing the dried carbon material with a nitrogen source to obtain a positive electrode host material precursor; and step 2, placing the positive electrode host material precursor in an oxygen-free environment, and performing high-temperature gas-phase nitrogen-doping heat treatment to obtain the nitrogen-doped carbon-based positive electrode host material. The application is that the nitrogen-doped carbon-based positive electrode host material is used as raw material to prepare a nitrogen-doped carbon-based positive electrode. The porous carbon material is modified through a simple and controllable high-temperature gas-phase nitrogen-doping strategy, and a high-performance nitrogen-doped carbon-based positive electrode host material is constructed. Meanwhile, with the aid of a physical confinement and chemical adsorption synergistic reinforcement mechanism, the rapid oxidation-reduction kinetics of iodine species on the positive electrode electrolyte interface is promoted, and the formation and shuttling of polyiodide ions are effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydroelectric energy storage technology, specifically to a nitrogen-doped carbon-based cathode host material, its preparation method, and its application. Background Technology

[0002] Against the backdrop of global energy transition, energy storage technology has become a core support for the safe and stable operation of new power systems and for increasing the proportion of renewable energy consumption. Lithium-ion batteries, with their high energy density and mature industrial foundation, have long held a dominant position in the energy storage market. However, they face increasingly prominent resource constraints, cost fluctuations, safety hazards, and environmental problems, prompting the industry to actively explore new alternative technologies.

[0003] Aqueous secondary batteries use aqueous solutions as electrolytes, offering significant advantages over traditional organic electrolyte systems, including inherent safety, environmental friendliness, and high ionic conductivity. Furthermore, their raw materials are abundant and inexpensive, effectively reducing reliance on scarce strategic resources and aligning with sustainable development principles. In addition, aqueous batteries have a smaller environmental impact throughout their entire lifecycle, from manufacturing to recycling, exhibiting superior ecological compatibility and making them highly compatible with the global green and low-carbon transformation trend.

[0004] However, aqueous batteries still have significant shortcomings: their energy density is generally lower than that of lithium-ion batteries, and their energy storage per unit volume is limited; in addition, they have problems such as a narrow electrochemical stability window, more electrode side reactions, and poor cycle life, which leads to their relatively limited large-scale application and practical engineering cases.

[0005] The theoretical specific capacity of elemental iodine can reach 211 mAh / g, while possessing approximately 1.38 V (vs Zn / Zn). 2+ The high discharge platform of zinc-iodine batteries is highly compatible with aqueous zinc-based battery systems. Furthermore, iodine is abundant in the Earth's crust and seawater, with seawater containing approximately 50-60 μg / L of iodine. This ample resource helps to further reduce the overall cost of zinc-iodine batteries. Therefore, zinc-iodine batteries fully inherit the advantages of aqueous batteries, making them an ideal energy storage system that combines high energy density, low cost, and environmental friendliness. However, this system still faces several key bottlenecks: iodine and its iodides have extremely poor conductivity, with a conductivity of only 10... -6 ~10 -9 The resistivity of elemental iodine is on the order of S / cm, and even higher at 1.3 × 10⁻⁶. 7 The high Ω·m content of iodine, coupled with its poor thermodynamic stability and tendency to sublimate, significantly increases the difficulty of large-scale electrode fabrication. During charge-discharge cycles, the polyiodide intermediates generated by the reaction are easily dissolved in the electrolyte by concentration gradients and shuttle between the positive and negative electrodes, leading to problems such as loss of active materials, severe self-discharge, and low coulombic efficiency.

[0006] In recent years, researchers have effectively promoted the immobilization of iodine species and prevented the shuttle movement of polyiodide ions by doping porous carbon-based materials with heteroatoms and designing catalytic sites. The research group of Professor Sun Xiaoming at Beijing University of Chemical Technology has developed a high-performance catalytic organic cathode by in-situ polymerization of melamine on activated carbon, accelerating the iodine ionization process. - / I 0 The direct conversion of polyiodides is achieved while suppressing the formation of polyiodides. Jinan University, addressing the core bottleneck of polyiodide ion shuttle and sluggish kinetics, designed and synthesized a ZrB2 / AC (zirconium boride / activated carbon) composite host. This utilizes the unsaturated Zr atoms on the ZrB2 surface to provide Lewis acid active sites, achieving strong chemisorption and efficient catalytic conversion of polyiodides. Furthermore, the three-dimensional microporous carbon framework iodine host material can also serve as a highly efficient iodine carrier in aqueous zinc-iodine batteries. However, all of the above works suffer from complex heteroatom doping preparation processes and difficulties in achieving a balance between performance and cost; moreover, for iodine-free cathode batteries where iodine species are entirely derived from iodine-based additives in the electrolyte, no doping method that can simultaneously balance cost and performance has been reported. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a nitrogen-doped carbon-based cathode host material, its preparation method, and its applications.

[0008] The technical solution of this invention to solve the aforementioned problem is to provide a method for preparing a nitrogen-doped carbon-based cathode host material, the method comprising the following steps: Step 1: Pre-treat the porous carbon material and then dry it to obtain the dried carbon material; then mix the dried carbon material with a nitrogen source evenly to obtain the cathode host material precursor. Step 2: Place the cathode host material precursor obtained in Step 1 in an oxygen-free environment and perform high-temperature gas-phase nitrogen doping heat treatment to obtain nitrogen-doped carbon-based cathode host material.

[0009] The technical solution of the present invention to solve the material technology problem is to provide a method for preparing the nitrogen-doped carbon-based cathode host material to obtain the nitrogen-doped carbon-based cathode host material.

[0010] The technical solution of the present invention to solve the aforementioned application problem is to provide an application of the nitrogen-doped carbon-based cathode host material, using the nitrogen-doped carbon-based cathode host material as a raw material to prepare a nitrogen-doped carbon-based cathode.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention modifies porous carbon materials through a simple and controllable high-temperature gas-phase nitrogen doping strategy to construct a high-performance nitrogen-doped carbon-based cathode host material. At the same time, through parameter control, the doping morphology and spatial distribution of nitrogen elements are effectively controlled. With the help of the physical confinement and chemical adsorption synergistic enhancement mechanism, the rapid redox kinetics of iodine species at the cathode electrolyte interface are promoted, while the formation and shuttle of polyiodide ions are effectively suppressed. Finally, a low-cost cathode host material with long cycle life and high specific capacity is prepared.

[0012] (2) This invention addresses the key technical bottlenecks in aqueous zinc-iodine battery systems by innovatively combining the dual advantages of electrolyte providing iodine source and nitrogen-doped carbon-based cathode host material modification to construct a novel electrode system that balances high areal capacity and high stability. It points out that although the configuration of iodine-free cathode and iodine species completely derived from electrolyte in traditional zinc-iodine batteries can achieve high areal capacity, it lacks an effective iodine fixation mechanism, resulting in severe iodide shuttle effect and low coulombic efficiency. While porous carbon-based composite iodine cathode can suppress the shuttle effect, it suffers from insufficient iodine loading and difficulty in improving areal capacity.

[0013] (3) This invention breaks through the inherent limitations of the two traditional schemes. It uses nitrogen-doped porous carbon as the positive electrode host material, and all iodine species are provided by the electrolyte. It retains the high areal capacity advantage of the electrolyte for iodine supply, and achieves efficient fixation of polyiodides through host material modification.

[0014] (4) The nitrogen-doped carbon-based cathode host material used in this invention has a well-developed multi-level pore structure and an extremely high specific surface area. The prepared nitrogen-doped carbon-based cathode host material can efficiently encapsulate elemental iodine and polyiodide ions in the electrolyte by means of physical confinement. At the same time, the abundant nitrogen active sites on the material surface can form a stable chemical interaction with iodine species, thereby achieving synergistic enhancement of physical confinement and chemical anchoring.

[0015] (5) The nitrogen-doped carbon-based cathode host material prepared by the present invention can effectively reduce the dissolution and loss of iodine components in the electrolyte, significantly suppress the polyiodide shuttle effect, achieve efficient and stable electrochemical energy storage output, and greatly improve the coulombic efficiency, cycle life and working reliability of zinc-iodine batteries. At the same time, with its well-developed pore structure, extremely high specific surface area, multi-level pore structure and abundant surface functional groups, it can achieve efficient physical encapsulation and chemical anchoring of iodine and polyiodide ions. The nitrogen active sites and iodine form a stable interaction, further enhancing the fixation ability of iodine, ensuring efficient and stable energy storage output and battery working reliability. Attached Figure Description

[0016] Figure 1 This is a SEM image of the nitrogen-doped carbon-based cathode host material of Example 1 of the present invention; Figure 2This is a SEM image of Ketjen Black in Comparative Example 1 of this invention. Figure 3 This is a TEM image of the nitrogen-doped carbon-based cathode host material of Example 1 of the present invention; Figure 4 This is a TEM image of Ketjen Black in Comparative Example 1 of this invention; Figure 5 This is a mapping diagram showing the elemental distribution analysis of the nitrogen-doped carbon-based cathode host material in Example 1 of the present invention. Figure 6 The Raman spectra of the nitrogen-doped carbon-based cathode host material of Example 1 and the Ketjen black of Comparative Example 1 are shown. Figure 7 The XRD spectra of the nitrogen-doped carbon-based cathode host material of Example 1 and the Ketjen black of Comparative Example 1 are shown below. Figure 8 This is a high-resolution N 1s XPS spectrum of the nitrogen-doped carbon-based cathode host material of Example 1 of the present invention; Figure 9 High-resolution N 1s XPS spectra and percentage distribution diagrams of different types of nitrogen elements are shown for the nitrogen-doped carbon-based cathode host materials in Examples 1, 3, and 4 of this invention. Figure 10 The graphs show the charge-discharge cycle performance of nitrogen-doped carbon-based zinc-iodine batteries in Examples 1 and 2 of this invention under a current density of 5 A / g. Figure 11 The graphs show the charge-discharge cycle performance of nitrogen-doped carbon-based zinc-iodine batteries in Examples 1 and 2 of this invention under a current density of 10 A / g. Figure 12 The graphs show the charge-discharge cycle performance of the nitrogen-doped carbon-based zinc-iodine cathode batteries of Examples 1, 3, and 4 of this invention and the Ketjen Black zinc-iodine cathode battery of Comparative Example 1 under a current density of 5 A / g. Figure 13 The graphs show the charge-discharge cycle performance of the nitrogen-doped carbon-based zinc-iodine cathode batteries of Examples 1, 3, and 4 of this invention and the Ketjen black zinc-iodine cathode battery of Comparative Example 1 under a current density of 10 A / g. Figure 14 This is a graph showing the areal capacity performance of the nitrogen-doped carbon-based positive electrode zinc-iodine battery of Example 1 of the present invention under long charge-discharge cycle at a current density of 10 A / g. Detailed Implementation

[0017] Specific embodiments of the present invention are given below. These specific embodiments are only used to further illustrate the present invention in detail and do not limit the scope of protection of the present invention.

[0018] This invention provides a method for preparing a nitrogen-doped carbon-based cathode host material (hereinafter referred to as the method), which includes the following steps: Step 1: Pre-treat the porous carbon material and then dry it to obtain the dried carbon material; then mix the dried carbon material with a nitrogen source evenly to obtain the cathode host material precursor. Preferably, in step 1, the porous carbon material is a commercially available porous carbon material, specifically one of activated carbon, Ketjen black, acetylene black, or carbon black (preferably Ketjen black).

[0019] Preferably, in step 1, the specific surface area of ​​the porous carbon material is 800~3000 m². 2 / g; of which, the specific surface area of ​​Ketjen Black is 800~1400m². 2 / g (preferably 800m) 2 / g).

[0020] Preferably, in step 1, the pretreatment process is as follows: grinding or high-energy ball milling (preferably grinding) at room temperature; grinding time is 1~20min (preferably 15min); high-energy ball milling speed is 200~500r / min (preferably 300r / min), and time is 1~3h (preferably 2h). The pretreatment has two functions: (1) refining and homogenizing the porous carbon material particles: crushing large carbon material particles to ensure closer contact between particles when mixed with nitrogen source, avoiding uneven doping due to excessively large particles; (2) optimizing the pore structure of porous carbon material: effectively breaking down amorphous carbon blocking the pore openings, which is beneficial for the active nitrogen species generated by the subsequent decomposition of melamine to enter the pores of porous carbon material.

[0021] Preferably, in step 1, the drying process is as follows: the temperature is 50~80℃ (preferably 65℃) and the time is 4~6h (preferably 5h).

[0022] Preferably, in step 1, the nitrogen source is melamine.

[0023] Preferably, in step 1, the mass ratio of nitrogen source to porous carbon material is 1~3:1~3 (preferably 2:1).

[0024] Preferably, in step 1, the process of uniform mixing is: grinding at room temperature for 1 to 20 minutes (preferably 15 minutes).

[0025] Step 2: Place the cathode host material precursor obtained in Step 1 in an oxygen-free environment and perform high-temperature gas phase nitrogen doping heat treatment by high-temperature gas phase method to obtain nitrogen-doped carbon-based cathode host material with high nitrogen content and high defect density.

[0026] Preferably, in step 2, the oxygen-free environment is an inert gas environment; the inert gas is argon or helium.

[0027] Preferably, in step 2, the high-temperature gas-phase nitrogen doping heat treatment process is as follows: the annealing temperature is 500~900℃ (preferably 550℃), the holding time is 2~6h (preferably 4h), and the flow rate of the inert gas is 100~300sccm (preferably 200sccm). It is preferably carried out in a tube furnace.

[0028] Preferably, step 2 specifically involves: placing the cathode host material precursor obtained in step 1 into a high-temperature resistant container (preferably a ceramic boat) that does not react with it, and then placing it in a closed heating environment (preferably a tubular furnace heating center) under vacuum to atmospheric pressure (i.e., 0~760 Torr); raising the temperature zone to 500~900℃ under a constant inert gas flow of 100~300 sccm for 2~6 hours; after the reaction is completed, allowing it to cool naturally to room temperature, stopping the gas flow to obtain a nitrogen-doped carbon-based cathode host material with high nitrogen content and high defect density.

[0029] This invention also provides a method for preparing nitrogen-doped carbon-based cathode host materials.

[0030] This invention also provides an application of a nitrogen-doped carbon-based cathode host material, which is used as a raw material to prepare a nitrogen-doped carbon-based cathode.

[0031] Preferably, the method for preparing a nitrogen-doped carbon-based cathode includes the following steps: S1. Mix the nitrogen-doped carbon-based cathode host material, conductive agent, binder and solvent evenly to obtain cathode slurry; Preferably, in step S1, the mass ratio of nitrogen-doped carbon-based cathode host material, conductive agent, and binder is 8:1 to 2:1 (preferably 8:1:1); the concentration of cathode slurry is 30 to 60 μL / mg (preferably 40 μL / mg).

[0032] Preferably, in step S1, the conductive agent is one of conductive carbon black, graphene, or carbon nanotubes (preferably conductive carbon black); the binder is polyvinylidene fluoride; and the solvent is N-methylpyrrolidone.

[0033] Preferably, in step S1, the process of achieving uniform mixing is as follows: stirring is used at a speed of 300~800 r / min (preferably 400 r / min) for 1~6 h (preferably 2 h) at room temperature. It is preferably carried out in a magnetic stirrer.

[0034] S2. The positive electrode slurry prepared in step S1 is uniformly coated on one surface of the current collector and then dried to obtain a nitrogen-doped carbon-based positive electrode.

[0035] Preferably, in step S2, the current collector is carbon felt, carbon cloth, or titanium foil (preferably carbon felt).

[0036] Preferably, in step S2, the drying process is as follows: temperature is 60~80℃ (preferably 65℃), and time is 1~2h (preferably 2h). It is preferably carried out in a vacuum drying oven.

[0037] Example 1: The preparation of nitrogen-doped carbon-based cathode host materials includes the following steps: Step 1: Take 2g of a substance with a specific surface area of ​​800m². 2 / g of Ketjen black was ground in a mortar for 15 minutes at room temperature and then dried at 65°C for 5 hours to obtain dried Ketjen black; then 4g of melamine was added to the mortar and ground at room temperature for 15 minutes until the mixture was uniform to obtain the precursor of the positive electrode host material. Step 2: Place the cathode host material precursor prepared in Step 1 in a tube furnace and perform high-temperature gas-phase nitrogen doping heat treatment at 550℃ under argon protection for 4 hours. The argon flow rate is 200 sccm to obtain the nitrogen-doped carbon-based cathode host material, namely nitrogen-doped Ketjen black material (abbreviated as N-KB material).

[0038] The preparation of nitrogen-doped carbon-based cathodes includes the following steps: Step S1: The prepared nitrogen-doped carbon-based cathode host material, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone are stirred at room temperature and 400 r / min for 2 h until they are uniformly mixed to obtain a cathode slurry; wherein, the mass ratio of nitrogen-doped carbon-based cathode host material, conductive carbon black and polyvinylidene fluoride is 8:1:1, and the concentration of cathode slurry is 40 μL / mg; Step S2: The cathode slurry prepared in step S1 is uniformly coated on one surface of a 1 mm thick carbon felt, and then dried in a vacuum drying oven at 65 °C for 2 h to obtain a nitrogen-doped carbon-based cathode.

[0039] The nitrogen-doped carbon-based positive electrode zinc-iodine battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The prepared nitrogen-doped carbon-based positive electrode is used as the positive electrode, zinc foil is used as the negative electrode, glass fiber membrane GF / D is used as the separator, and 160 μL of a mixed solution of 1M NaI and 2M Zn(TfO)2 is used as the electrolyte.

[0040] Battery assembly: Assemble the button cell in the following order: negative electrode shell - spring piece - gasket - negative electrode - electrolyte - separator - electrolyte - positive electrode - positive electrode shell. The battery shell specification is 2032, resulting in a nitrogen-doped carbon-based zinc-iodine positive electrode battery.

[0041] Example 2: This embodiment is exactly the same as Embodiment 1, except that in step 1, the porous carbon material is activated carbon, and nitrogen-doped carbon-based cathode host material is obtained, namely nitrogen-doped activated carbon material (abbreviated as N-AC material).

[0042] Example 3: This embodiment is exactly the same as Embodiment 1, except that in step 1, the mass ratio of Ketjen Black to melamine is 1:1.

[0043] Example 4: This embodiment is exactly the same as Embodiment 1, except that in step 1, the mass ratio of Ketjen Black to melamine is 2:1.

[0044] Comparative Example 1: The preparation of the Ketjen Black cathode includes the following steps: Step S1: Ketjen black, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone are stirred at 400 r / min for 2 h at room temperature until they are uniformly mixed to obtain a positive electrode slurry; wherein, the mass ratio of Ketjen black, conductive carbon black and polyvinylidene fluoride is 8:1:1, and the concentration of the positive electrode slurry is 80 μL / mg. Step S2: The positive electrode slurry prepared in step S1 is uniformly coated on one surface of a 1 mm thick carbon felt, and then dried in a vacuum drying oven at 65 °C for 2 h to obtain the Ketjen Black positive electrode.

[0045] The Ketjen black positive electrode zinc-iodine battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The prepared Ketjen black positive electrode is used as the positive electrode, zinc foil is used as the negative electrode, glass fiber membrane GF / D is used as the separator, and 160 μL of a mixed solution of 1M NaI and 2M Zn(TfO)2 is used as the electrolyte.

[0046] Battery assembly: Assemble the button cell in the following order: negative electrode shell - spring piece - gasket - negative electrode - electrolyte - separator - electrolyte - positive electrode - positive electrode shell. The battery shell specification is 2032, resulting in a Ketjen black positive electrode zinc-iodine battery.

[0047] Performance testing: Charge-discharge cycle tests were conducted on the nitrogen-doped carbon-based zinc-iodine cathode batteries of Examples 1-4 and the Ketjen black zinc-iodine cathode battery of Comparative Example 1.

[0048] Depend on Figure 1 As can be seen, in Example 1, after high-temperature gas-phase nitrogen doping heat treatment, the N-KB material still successfully maintained its inherent porous structure, without obvious structural collapse or sintering. This indicates that the high-temperature gas-phase nitrogen doping process has little damage to the morphology and structure of carbon materials and can retain the physical confinement advantage of the carbon substrate.

[0049] Depend on Figure 2 As can be seen, the Ketjen Black (KB) in Comparative Example 1 all exhibit a typical porous aggregated structure, which is a structure formed by the aggregation of nano-sized particles, with high specific surface area and abundant pore structure.

[0050] Depend on Figure 3 It can be seen that the N-KB material has clear amorphous carbon structure characteristics, and short-range ordered lattice stripes can be seen in some areas, indicating that the material still maintains a certain degree of graphitization after nitrogen doping, which is beneficial to electron transport.

[0051] Depend on Figure 4 It can be seen that pure KB material exhibits typical amorphous carbon structure characteristics, with microstructure mainly consisting of particle agglomeration and localized weak short-range lattice fringes. This indicates that pure Ketjen black itself possesses a certain degree of graphitization and excellent intrinsic conductivity, and its regular carbon skeleton can provide an ideal structural substrate for subsequent nitrogen doping modification.

[0052] Depend on Figure 5 It can be seen that nitrogen is highly uniformly distributed in the carbon matrix, and no obvious nitrogen agglomeration phenomenon is observed. This confirms that the high-temperature gas-phase nitrogen doping strategy can achieve uniform nitrogen doping, laying the foundation for the formation of uniform active sites.

[0053] Depend on Figure 6 It can be seen that the D peak (~1350 cm⁻¹) in the Raman spectrum of carbon materials -1 ) and G peak (~1580cm) -1 The intensity ratio I(D) / I(G) reflects the degree of defect in carbon materials. The I(D) / I(G) ratio of the pure KB material in Comparative Example 1 is 1.15, while the I(D) / I(G) ratio of the N-KB material in Example 1 is increased to 1.3. This indicates that the introduction of nitrogen atoms creates more defect sites in the carbon framework. These defect sites not only provide active centers for iodine adsorption but also enhance the chemical interaction with polyiodides. Simultaneously, the G peak position of the N-KB material shifts towards lower wavenumbers, further confirming that nitrogen doping alters the electronic structure and lattice vibrational properties of carbon materials, providing a structural basis for improving the adsorption and catalytic performance of iodine species.

[0054] Depend on Figure 7 It can be seen that the pure KB in Comparative Example 1 exhibits characteristic diffraction peaks of graphitic carbon at 2θ = 24.5° and 43.3°, corresponding to the (002) and (100) crystal planes, indicating that the commercial porous carbon material has a certain degree of graphitization. The (002) peak of the N-KB material in Example 1 shifts to a higher angle and narrows, indicating that the introduction of melamine promotes the transformation of the carbon material from disordered amorphous carbon to short-range ordered graphitic carbon, gradually increasing the degree of graphitization, which helps to enhance the electronic conductivity of the material. Furthermore, no new characteristic diffraction peaks appeared in the XRD pattern of the N-KB material, indicating that nitrogen entered the carbon framework in the form of doping without forming an independent nitride crystal phase, confirming the success of nitrogen doping.

[0055] Depend on Figure 8As can be seen, the XPS analysis results further confirmed the successful doping of nitrogen and the existence of different nitrogen configurations. The N 1s high-resolution spectrum can be divided into three characteristic peaks, corresponding to pyridine nitrogen (398.11 eV), pyrrole nitrogen (399.88 eV), and oxidized nitrogen (403.57 eV), respectively. Among them, pyridine nitrogen has the highest proportion, reaching 65% in the N-KB material of Example 1. Pyridine nitrogen is a nitrogen atom at the edge or defect of carbon material, which is bonded to two carbon atoms and has a lone pair of electrons. It can act as an effective electron donor and interact strongly with elemental iodine (I2) to form a stable complex structure, thereby inhibiting the dissolution and shuttle of polyiodide ions during charging and discharging.

[0056] Depend on Figure 9 It can be seen that the nitrogen content first increases and then levels off with the increase of the nitrogen source ratio, reaching a maximum of 7.8% at 2:1 in Example 1 (i.e., the mass ratio of nitrogen source to porous carbon material is 2:1). The nitrogen configuration differs significantly under different ratios: the proportion of pyridine nitrogen reaches a peak of 65% at 2:1 (Example 1), while the proportions at 1:1 (Example 3) and 1:2 (Example 4) are significantly lower; the proportion of pyrrole nitrogen gradually decreases with increasing nitrogen source ratio, while the proportion of oxidized nitrogen increases slightly. The results indicate that at low doping levels, nitrogen atoms mainly exist in the active nitrogen configuration at defect sites; excessive nitrogen source is difficult to effectively dope, and instead increases the amount of ineffective oxidized nitrogen. Therefore, a mass ratio of melamine to porous carbon material of 2:1 is the optimal doping ratio, possessing both the highest total nitrogen content and the highest pyridine nitrogen proportion, providing sufficient active sites and significantly enhancing the adsorption and catalytic ability of polyiodides.

[0057] In this invention, Figures 10-14 The specific capacity (mAh / g) and current density (A / g) are calculated based on the mass of the cathode host material and are used only to compare the performance of the cathode host material. It should be noted that the iodine redox active species in this system are entirely derived from the electrolyte, and the cathode only acts as a catalyst support and current collector, and does not contribute to the capacity itself.

[0058] Depend on Figure 10 It can be seen that the electrochemical performance of Example 1 is comprehensively superior to that of Example 2: at a current density of 5 A / g, the initial specific capacity of Example 1 is 550 mAh / g, and the capacity retention rate exceeds 96% after 1200 cycles; the initial specific capacity of Example 2 is 420 mAh / g, and the capacity retention rate is approximately 90% after 800 cycles. This difference stems from the higher specific surface area, superior intrinsic conductivity, and more developed pore structure of Ketjen Black, which enables more adequate iodine loading, faster reaction kinetics, and more effective suppression of polyiodide shuttle. Coulombic efficiency (%) Depend on Figure 11As can be seen, at a current density of 10 A / g, the initial specific capacity of Example 1 is 520 mAh / g, the capacity retention rate is over 92% after 2500 cycles, and the coulombic efficiency is stable at over 98%; the initial specific capacity of Example 2 is 380 mAh / g, and the capacity retention rate is only 63% after 4500 cycles, further verifying the superiority of Ketjen Black as a carbon substrate.

[0059] Depend on Figure 12 It can be seen that Example 1 exhibits the best performance: at a current density of 5 A / g, the initial specific capacity reaches 550 mAh / g, and the capacity retention exceeds 96% after 1200 cycles. Example 2 shows the second best performance, while Example 3, due to insufficient nitrogen doping and a lack of active sites, has significantly inferior capacity baseline and rate performance compared to Example 1. This result confirms that a melamine to Ketjen black mass ratio of 2:1 is the optimal doping ratio, achieving the best balance between the number of active sites, conductivity, and pore structure.

[0060] Depend on Figure 13 As can be seen, at a current density of 10 A / g, the initial specific capacity of Example 1 is about 520 mAh / g, the capacity retention rate is over 92% after 2500 cycles, and the coulombic efficiency is stable at over 98%, further verifying the superiority of Example 1.

[0061] Depend on Figure 14 It can be seen that the areal capacity remains stable at approximately 1.5 mAh / cm³. 2 After more than 8000 consecutive charge-discharge cycles, the capacity retention rate remained close to 100%, with no significant capacity decay. The coulombic efficiency remained stable at approximately 100%, exhibiting only minor fluctuations during cycling without significant decrease or drop. This result demonstrates that the nitrogen-doped carbon-based cathode host material prepared in this invention can effectively suppress the polyiodide shuttle effect under high areal capacity and high current density conditions through the synergistic effect of physical confinement and chemisorption at nitrogen sites, while maintaining a stable electrode structure and rapid reaction kinetics. This results in ultra-long cycle life and near 100% capacity retention, providing reliable performance support for the practical application of zinc-iodine batteries in large-scale energy storage.

[0062] Any aspects not covered in this invention are applicable to existing technologies.

Claims

1. A method for preparing a nitrogen-doped carbon-based cathode host material, characterized in that, The method includes the following steps: Step 1: Pre-treat the porous carbon material and then dry it to obtain the dried carbon material; then mix the dried carbon material with a nitrogen source evenly to obtain the cathode host material precursor. In step 1, the porous carbon material is Ketjen Black; the specific surface area of ​​the porous carbon material is 800~3000 m². 2 / g; The mass ratio of nitrogen source to porous carbon material is 2:1; In step 1, the pretreatment process is: grinding at room temperature to refine the particles of porous carbon material and optimize the pore structure of porous carbon material; In step 1, the drying process is as follows: temperature is 50~80℃, and time is 4~6h; In step 1, the nitrogen source is melamine; Step 2: Place the cathode host material precursor obtained in Step 1 in an oxygen-free environment and perform high-temperature gas-phase nitrogen doping heat treatment to obtain nitrogen-doped carbon-based cathode host material. The process of high-temperature gas-phase nitrogen doping heat treatment is as follows: annealing temperature is 550℃, holding time is 2~6h, oxygen-free environment is inert gas environment, and inert gas flow rate is 100~300sccm.

2. The method for preparing the nitrogen-doped carbon-based cathode host material according to claim 1, characterized in that, In step 1, the grinding time is 1~20 minutes.

3. The method for preparing the nitrogen-doped carbon-based cathode host material according to claim 1, characterized in that, In step 1, the process for achieving uniform mixing is: grinding at room temperature for 1~20 minutes.

4. The method for preparing the nitrogen-doped carbon-based cathode host material according to claim 1, characterized in that, In step 2, the inert gas is argon or helium.

5. The method for preparing the nitrogen-doped carbon-based cathode host material according to claim 1, characterized in that, Step 2 specifically involves placing the cathode host material precursor obtained in Step 1 into a high-temperature resistant container that does not react with it, and then placing it in a sealed heating environment under vacuum to atmospheric pressure. Under a constant flow of inert gas at a flow rate of 100~300 sccm, the temperature zone is raised to 550℃ and held for 2~6 hours. After the reaction is completed, the material is allowed to cool naturally to room temperature, and then the gas flow is stopped to obtain the nitrogen-doped carbon-based cathode host material.

6. A nitrogen-doped carbon-based cathode host material prepared by the method described in any one of claims 1-5.

7. The application of the nitrogen-doped carbon-based cathode host material according to claim 6, characterized in that, Using the nitrogen-doped carbon-based cathode host material as a raw material, a nitrogen-doped carbon-based cathode is prepared.

8. The application according to claim 7, characterized in that, A method for preparing a nitrogen-doped carbon-based cathode includes the following steps: S1. Mix the nitrogen-doped carbon-based cathode host material, conductive agent, binder and solvent evenly to obtain cathode slurry; S2. The positive electrode slurry prepared in step S1 is uniformly coated on one surface of the current collector and then dried to obtain a nitrogen-doped carbon-based positive electrode.

9. The application according to claim 8, characterized in that, In step S1, the mass ratio of nitrogen-doped carbon-based cathode host material, conductive agent, and binder is 8:1 to 2:1; In step S1, the conductive agent is one of conductive carbon black, graphene, or carbon nanotubes; the binder is polyvinylidene fluoride; and the solvent is N-methylpyrrolidone. In step S1, the process of achieving uniform mixing is as follows: stirring is used at a speed of 300~800 r / min for 1~6 h at a temperature of room temperature.

10. The application according to claim 8, characterized in that, In step S2, the current collector is carbon felt, carbon cloth, or titanium foil; In step S2, the drying process is as follows: temperature is 60~80℃, and time is 1~2h.